Prevalence and Practices of Self-medication With Antibiotics Among Nursing Students at a Training Institution in Western Uganda - Nankya, Shanitah; Musinguzi, Puis; Arishaba, Adella; Najjuma, Josephine Nambi (Research square, 2023)
Background: Self-medication is one of the leading causes of inappropriate antibiotic use practices. This leads to antimicrobial resistance which results into anti-microbial related deaths. The aim of the study was to determine the self-medication practices and their prevalence among nursing students at certificate and diploma level at a health training institution in south western Uganda. Methods: A descriptive cross-sectional study design was used. Data was collected using self-administered questionnaires among certificate and diploma nursing students. A total of 358 nursing students participated in the study. Results: More than half of the nursing students, 85.7% (307) reported to have practiced self-medication. It was also noted that 91.5 % (237) and 69.5% (66) of certificate nursing students diploma nursing students respectively practiced self-medication. Most students, 50.8% (182) based their choice of the antibiotic to use on own experience with the antibiotic used before. Also 39.9% (143) students reported to have been getting their antibiotics mainly from the community pharmacist and 31.4% (112) from drug shop. The most commonly used antibiotics for self-medication included amoxyl and metronidazole. Change of dosage during course of treatment and switching of antibiotics during course of treatment were some of the self-medication was reported. Conclusion: Self-medication practices are very common among nursing students. It is a major public health problem as it is associated with inappropriate antibiotic use practices, antimicrobial resistance and related deaths.
Keywords: Self-medication; Nursing students; Antibiotics; Practices